Socioeconomic Factors and The Incidence of Maternal and Child Leprosy: A Study in Endemic Areas in East Java, Indonesia - Hari Basuki Notobroto; Flora Ramona Sigit Prakoeswa; Anang Endaryanto; Cita Rosita Sigit Prakoeswa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Leprosy is one of the neglected tropical disease caused by Mycobacterium leprae. Endemicareas are still found due to incapability of MDT regimen alone to eradicate leprosy. The good understandingof high-risk population characteristic to plan elimination strategy of leprosy is needed, especially invulnerable populations such as mothers and children population. This study aims to find association betweensocioeconomic factors and the incidence of leprosy in maternal and children leprosy in endemic areas.Methods: This is a case-control study in endemic areas in Tuban Regency, East Java Province, Indonesia.The obtained data was done using structured questionnaire and direct measurement. Chi-square, t-test/Mann-Whitney test was used to assess the association between socioeconomic factors and the incidence ofleprosy in maternal and children leprosy in endemic areas.Results: 22 pairs of cases and 57 pairs of controls were analyzed. This study found that education isassociated with the incidence of leprosy. Significant results were observed in father’s education (p value=0.023) with the incidence of maternal leprosy and mother’s education (p value= 0.003) education) andfather’s education (p value= 0.013) with the incidence of children leprosy. Family income also associatedwith the incidence of maternal (p value= 0.040) and children leprosy (p value= 0.036). Occupation is notassociated with the incidence of leprosy.Conclusion : The result of this study shows that education and family income are related with the incidenceof leprosy in both, mothers and children population.